PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK PADA MATA PELAJARAN MATEMATIKA SISWA KELAS II SDN CANGKUDU 03 KABUPATEN TANGERANG - Ria Rosita; Een Unaenah; Dilla Fadhillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on mathematics learning on spatial geometry, teachers still use makeshift learning media. The research was conducted to produce Pop Up Book media for spatial geometry mathematics in class II. The main objective of this research is to determine the validity and effectiveness of a Pop Up Book learning media for mathematics on spatial geometry for class II SDN Cangkudu 03 Tangerang Regency. This research uses the Research and Development (R&D) method using the ADDIE model which consists of five stages: (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques used are observation, interviews, and questionnaires. Quantitative and qualitative data are analyzed using a Likert Scale with an assessment score of 1-5. The results of this research and development show that according to material experts, the validity level is 89.3% of the "Eligible" criteria, and according to media experts the validity level is 87.1% of the "Eligible" criteria, and according to educators/teachers the validity level is 92.7% of the "Very Eligible" criteria, student responses in one-to-one group trials obtained a percentage of 82.6% of the "Very Eligible" criteria, small group trials obtained a percentage of 95.7% of the "Very Eligible" criteria, large group trials obtained a percentage of 96.5% of the "Very Eligible" criteria from the results of the student test obtained a percentage of 85.75 of the "Very Effective" criteria which indicates that the Pop Up Book learning media is considered good and feasible to use. Based on the results of the study, it can be concluded that the Pop Up Book learning media for mathematics on spatial geometry material in class II is very feasible in terms of validity and effectiveness to be used as a learning medium in class II of SDN Cangkudu 03 Tangerang Regency.